Epidemiological analysis of rabies in herbivores in the region of Araçatuba – São Paulo, Brasil: preliminary results - Alves, A. J. S.; Carvalho, C.; Casagrande, D. K. A.; Souza Filho, V. N.; Pedro, W. A.; Queiroz, L. H. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is a major zoonosis of great impact on both economic and public health and veterinary medicine. Rabies in herbivores is distributed in almost all Latin American countries and its control constitutes a major challenge for Livestock Defense. This study aims to make an epidemiological analysis of Rabies in herbivores in rural areas of most municipalities included in the Office of Agriculture and Livestock Defense Araçatuba (EDA). To this end, an epidemiological questionnaire was elaborated and applied to obtain information related to rabies in herbivores. The following variables were analyzed: presence, frequency and period of occurrence of bat bites marks on the animals, the presence and types of shelters for bats; recent occurrence of death of animals with neurological signs on the property, use of vaccine against rabies, use of methods for bats control and environmental change in the area of the property. The results show that out of 111 properties sampled, 23.4% of them observed marks of bat biting in the animals, and of these, 23% observed the marks of bites daily, 4% weekly, 8% monthly and 65% rarely. The observation of bite marks occurs more during the rainy season (73.1%). 11.7% of owners surveyed report the presence of shelters of bats and the main types of shelters are abandoned houses (38%), hollow trees (38%) and others (15%). Only 70.9% of those surveyed vaccinate the animals against rabies and 76.32% of these vaccinate the entire herd. In 4.5% of the properties it was reported the use of some method for the control of bats. Approximately 60% of properties had some kind of environmental change, particularly with respect to the advance of sugarcane in the region. The quantitative variables studied were the number of animals in the properties sampled, according to the kind, with an average of 243 animals per farm (237 cattle and six horses) and median 93 (90 and 3), respectively. We also performed the association between properties where it was found seropositive bats with the variables of the questionnaires, by the method of chi-square test or Fisher. The variables that showed a strong association with seropositivity of bats were the presence of shelter and vaccination. All statistical analyzes were performed using SPSS 20.0. In each of the properties were obtained geographic coordinates using a GPS, allowing a spatial characterization by plotting the points with the help of the program ARCGIS 10.0.